A clinical study on peripartum cardiomyopathy at tertiary care hospital - Garag, Seeta S.; D., Vinay Raju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cardiac diseases complicate 1-4% of pregnancies in women without pre-existing cardiac abnormalities. Cardiac disease in the pregnant woman can present a challenge to the obstetrician, cardiologist and neonatologist. Peripartum cardiomyopathy (PPCM) is an idiopathic disorder defined as heart failure occurring in women during the last month of pregnancy and up to 5 months postpartum. Aim is to study the burden of the disease, maternal outcome in PPCM. Methods: The present study was conducted among the antenatal women admitted in the department of Obstetrics and Gynecology at KIMS, Hubli with a previously diagnosed cardiac disease or diagnosed after admission during index pregnancy from December 2016 to May 2018. The mothers were followed up till discharge. Maternal outcome was noted as discharged or died. Results: A total of 11 cases of PPCM noted in our study out of which one case was developed before delivery, and 10 cases developed postnatally. Out of ten cases which were developed postnatally, 5 patients died giving around 50% of mortality rate. Conclusions: PPCM affects previously normal healthy women in the last month of pregnancy and up to 5 months after delivery. Careful assessment of risk factors contributing PPCM could help in their prevention. And these patients should be stratified in developing PPCM in future pregnancies through proper tools available.